Adsorption isotherms modeling of herbicides bispyribac- sodium and metribuzin on two common Egyptian soil types - Fouad, Mohamed R; El- Aswad, Ahmed F; Badawy, Mohamed E. I.; Aly, Maher I. (Journal of agricultural, environmental and veterinary sciences, 2019)
The experimental adsorption isotherms of tested pesticides BPS and MBZ from aqueous solution onto clay loam soil and sandy loam soil. The order of adsorption on clay loam soil and sandy loam soil is: BPS > MBZ. Ten isotherm models: Langmuir (five linear forms), Freundlich, Temkin, Dubinin- Radushkevich (D- R), Elovich, Fowler- Guggenhiem, Kiselev, Jovanovic, Harkin- Jura and Halsey models were applied to experimental data of tested pesticides; BPS and MBZ in clay loam soil and sandy loam soil. It was observed that the values of Langmuir parameters obtained from different linear expressions were different. The values of the coefficient of correlation obtained from different Langmuir expressions indicate that the soil type is the essential factor affecting on the suitable model expression. Low determination coefficient values of tested pesticides in different soils were obtained from all Langmuir expressions except the coefficient values of Langmuir 3 and 4 for MBZ in clay loam. The Freundilch model has agreement with experimental data for MBZ and BPS in clay loam soil, for MBZ and BPS in sandy loam. The adsorption data for tested pesticides in soils were analyzed by a regression analysis to test their fit with Temkin isotherm model. This model perfectly describes the adsorption isotherms of BPS in clay loam soil and sandy loam soil because of the higher coefficients of correlations and lower standard error values while it is invalid to describe the adsorption isotherm of MBZ in different tested soils. Dubinin- Radushkevich (D- R) isotherm model it was observed that the coefficient of correlation values were low, therefore, this model does not suitable to describe the equilibrium data for tested pesticides in different. Elovich model It was observed that the coefficients of correlation are low (< 0.86) for tested pesticides in tested soils indicating a bad linearity.The calculated values of θ depend on the Freundlich model are lower than 0.6. Therefore, the Fowler- Guggenheim model could be used to describe the adsorption of the tested pesticides. Jovanovic model the coefficient values of the tested pesticides BPS and MBZ were 0.7971, and 0.9130 in clay loam soil, 0.9144 and 0.9077 in sandy loam soil.The adsorption data for the tested pesticides in different tested soils were analyzed by a regression analysis to fit the equation of Harkin- Jura isotherms.Halsey isotherm is suitable for the experimental results.